Parsley Root—Petroselinum crispum (Mill.) Nym. (Tuberosum group) - James M. Stephens (EDIS)
This document describes parsley root (Petroselinum crispum, Tuberosum group), a vegetable valued for both its edible leaves and parsnip-like root. It outlines the plant’s culinary uses, particularly in European cuisines, and provides guidance on cultivation practices suitable for Florida’s cool seasons. Original publication date May 1994.